Public Services in Election of Regional Chairman - Evy Yuliati; Widayati Widayati (Law Development Journal, 2021)
The purpose of this article is to describe the form of implementation or public services in regional head elections. This problem is related to several related theories, such as constitutional law theory, democratic law theory, people's sovereignty law theory. This article also discusseslaw and public policies implemented in the elections in Indonesia. MethodThe research used in writing this article is a type of normative legal research. The results of the study indicate that legal theory and public policy are needed in Indonesia. This is done as a basis for implementing democratic practices. The form of implementing laws in constitutional theory is that the KPU establishes KPU Regulations and KPU Decrees in the implementation of Pilkada and provides solutions to problems of implementing law that are contrary to KPU regulations. The mechanism is if there is a PKPU which is deemed contrary to the Election Law, then the examination will be carried out at the Supreme Court in accordance with the provisions in Article 9 paragraph (2) of Act No. 12 of 2011. The implementation of the theory of democratic law in Indonesia is by holding general elections to elect leader, starting from the regional level to the national level. These activities are carried out in order to realize the government system that the people want. The implementation of the theory of popular sovereignty in the Pilkada is the determination of the victory of a candidate for regional head which is determined based on the number of valid votes based on applicable law. The theory of sovereignty also contributes to implementing a democratic system through the principles of people's sovereignty. The conclusion from this research is that the theories that play a role in the implementation of the Pilkada include the theory of democracy, the theory of the constitution, and the theory of people's sovereignty. The three theories are interrelated to support the implementation of Pilkada in accordance with democratic principles. In addition, there are three levels of public policy, namely macro, meso, and micro public policies.